In search of radio emission from exoplanets: GMRT observations of the binary system HD 41004. Issue 4 (17th November 2020) - Narang, Mayank; Manoj, P; Ishwara Chandra, C H; Lazio, Joseph; Henning, Thomas; Tamura, Motohide; Mathew, Blesson; Ujwal, Nitish; Mandal, Pritha
ABSTRACT: This paper reports Giant Metrewave Radio Telescope (GMRT) observations of the binary system HD 41004 that are among the deepest images ever obtained at 150 and 400 MHz in the search for radio emission from exoplanets. The HD 41004 binary system consists of a K1 V primary star and an M2 V secondary; both stars are host to a massive planet or brown dwarf. Analogous to planets in our Solar system that emit at radio wavelengths due to their strong magnetic fields, one or both of the planet or brown dwarf in the HD 41004 binary system are also thought to be sources of radio emission. Various models predict HD 41004Bb to have one of the largest expected flux densities at 150 MHz. The observations at 150 MHz cover almost the entire orbital period of HD 41004Bb, and about 20 per cent of the orbit is covered at 400 MHz. We do not detect radio emission, setting 3σ limits of 1.8 mJy at 150 MHz and 0.12 mJy at 400 MHz. We also discuss some of the possible reasons why no radio emission was detected from the HD 41004 binary system.